The Influence of Eco-friendly Ash on Sustainable Construction Material: A Review - Prabagar, S.; Suganja, T.; Jasotha, P. (Applied Science and Innovative Research, 2022)
Nowadays climate change is one of the major concerning factors due to increasing temperature throughout the world. Carbon dioxide is a significant gas in the greenhouse effect which leads to global warming. The construction industries released 40% carbon emissions from thermal calcium carbonate decomposition especially in cement production and combustion of fossil fuels of non-renewable energy. Renewable energy acts a vital part in the evolution of sustainability. Bioenergy has been deliberated carbon neutral as the released carbon is absorbed by flora. This paper presents a comprehensive review of the pozzolanic properties of waste ash and the performance of concrete. Ash is a by-product produced from various resources such as rice husk, wood, coal, sawdust combustion, etc. Waste ash is reused as supplementary material in eco-friendly concrete production. This helps for the disposal of waste as well as contributes the sustainability by reducing carbon emission into the environment
Keywords: Eco-friendly concrete; Waste ash; Pozzolanic properties; Review